(untitled) (Acta Polytechnica CTU Proceedings, 2016)
September 18th, 2016 Deggendorf, Germany http://robotics.fel.cvut.cz/pair16/ Organized by: Artificial Intelligence Center Department of Computer Science Faculty of Electrical Engineering Czech Technical University in Prague Technicka 2, Prague 6, 166 27, Czech Republic Guest editors: Jan Faigl (Artificial Intelligence Center, Department of Computer Science, Faculty of Electrical Engineering, Czech Technical University in Prague) Jiří Vokřínek (Artificial Intelligence Center, Department of Computer Science, Faculty of Electrical Engineering, Czech Technical University in Prague) Scientific comittee: D. Belter (Poznań University of Technology, Poland) W. Dorner (Technische Hochschule Deggendorf, Germany) J. Faigl (Czech Technical University in Prague) T. Krajník (University of Lincoln, United Kingdom) A. Komenda (Czech Technical University in Prague) G. Kupris (Technische Hochschule Deggendorf, Germany) M. Rollo (Czech Technical University in Prague) M. Saska (Czech Technical University in Prague) J. Vokřínek (Czech Technical University in Prague) V. Vonásek (Czech Technical University in Prague) K. Walas (Poznań University of Technology, Poland) Foreword: The third year of the student conference on “Planning in Artificial Intelligence and Robotics” (PAIR) continues in joining young researchers and students interested in robotics and artificial intelligence. In 2016, we follow the schema of the last year as a joint event with the RoboTour competition in Deggendorf, Germany. Thanks to the great collaboration with Gerald Kupris and Wolfgang Donner from Technische Hochschule Deggendorf and support from Czech Technical University under project No. SVK 26/16/F3 and Bayerisches Staatsministerium der Finanzen, für Landesentwicklung und Heimat, we have been able to provide accommodations and travel support to participants and an invited speaker. Fourteen papers have accepted and listed in the conference program. The papers have been authored by students from Central Europe, in particular from Czechia, Germany, Poland, and Slovakia. Regarding this, the conference continues with addressing a broader audience and not only students from Czech universities. During the student talks, it has been satisfactory to see young researchers how they acquired experience with presenting their ideas and share results with the audience. The topics of the student presentations range from fundamental problems of mobile robotics such simultaneous localization and mapping, planning algorithms, decentralized exploration but also address high-level data managing for guiding humans or autonomous vehicles. Six papers have been selected for the proceedings and you can read students work about autonomous robot control in robotic competitions, communications frameworks in multi-robot systems, map building, localization of hexapod crawling robot and its energy efficiency using various motion gaits, and multi-goal planning for unmanned aerial vehicles. These papers have been mostly written by undergraduate students, and it is my great pleasure to see how they put their results into a form of research papers. Hopefully, it will provide them nice experience and courage them to further research and scientific work. The format of the conference as a joint event with the RoboTour competition proves to be very vital and interesting for young researchers. Based on the positive feedback and interest from the international young research community, it encourages me to continue with the conference for the next year. I would like to thank all the authors for high-quality presentations and final versions of the articles presented in the proceedings. Thank you all, Jan Faigl